(untitled) (FUDMA JOURNAL OF SCIENCES, 2022)
Crop planting is an indispensable farm operation to increase production through the proper facilitation of optimum plant population per area as well as reducing unnecessary competition among crops. The excessive inaccurate placement of seed at a required depth and intra - row distance, low field capacity and seed damage due to metering all envisage the need for a locally developed and cost effective multi-row animal drawn precision seed planter. This study focused on the design, fabrication and performance evaluation of a four row animal drawn maize seed planter. The fabrication was carried out at the Department of Agricultural and Bio-Resources Engineering Workshop, Ahmadu Bello University Zaria. The machine was evaluated in the experimental field of the department during the 2019 raining season. Three levels of planting speed ‘S’, three levels of hopper seed quantity ‘W’ and two levels of planting depth ‘D’ were assessed. The field experiment was designed in a 3×3×2 randomized complete block design (RCBD). The results showed that the effects of planting speed, seed quantity and planting depth were significant on the planting performance of the machine. The highest mean seed spacing, germination counts, field capacity and seed delivery rate of 23.50 cm, 88.5 %, 0.54 ha/hr and 20.7 kg/ha respectively were obtained. The developed planter has successfully eliminated the limitations associated with manual planting method, most locally developed planters, imported tractor drawn planters as well as increasing the field capacity of the planting operation.